2020
DOI: 10.1002/rcm.8993
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ‐based quantitative proteomics analysis of immune thrombocytopenia patients before and after Qishunbaolier treatment

Abstract: RationaleTreatment of immune thrombocytopenia (ITP) usually involves long‐term use of immunosuppressive corticosteroids and splenectomy. However, these treatments often have side effects in patients. The Mongolian medicine Qishunbaolier (QSBLE) has a high curative effect, reduces the chances of relapse, and has no obvious side effects. This study was designed to identify potential therapeutic targets of QSBLE for treating ITP.MethodsTo reveal differences in protein expression between ITP patients (ITPs) before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…QSBLE is a Mongolian medicine reported to recover platelet count with minimal side effects. Collectively, both studies identified miRNA and proteins that were differentially expressed but were not able to explain the mechanism of QSBLE in ITP [ 163 , 164 ].…”
Section: Discussionmentioning
confidence: 99%
“…QSBLE is a Mongolian medicine reported to recover platelet count with minimal side effects. Collectively, both studies identified miRNA and proteins that were differentially expressed but were not able to explain the mechanism of QSBLE in ITP [ 163 , 164 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Gene Ontology (GO) terms and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways 39,40 are used for predicting the roles of underlying targets in gene function and signaling pathways. Thus, GO and KEGG were used in the present study using DAVID 6.8 (https://david.ncifcrf.gov/; accessed March 5, 2021) 41 to explore the mechanisms underlying ZZMRP in the treatment of constipation.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the multiple mechanisms of AM against cisplatin-induced kidney damage at the systematic level further, we used DAVID 6.8 ( https://david.ncifcrf.gov/ , March 5, 2021) [ 31 ] to perform the functional enrichment analysis of core targets, including the Gene Ontology (GO) terms as well as Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%